(3TQM GdEjLj Ydi eNJUQ GHf GdMGLHs - (3GdEjLj, CHh GdaVd, YVO GdOjf, YHO GdQMef Hf CMeO Hf YHO GdZaGQ, J (B756(3g`s
(3ChdgG (B:s
(3HJQ LRA ef GdaGJMI, hChd GdehLhO efg(B: (3hCaQOhG dPdc YdeG Sehg CUhd Gdabg(B...s
(3BNQgG (B:s
(3eHJhQI GdBNQ , hBNQ GdehLhO efgG(B: ... (3hjJQcH ef GdJQLjMGJ aj GdeQcHGJ hGdMOhO(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B3(3,U(B295s
(3cTa GdXfhf(B:(3L(B2(3,U(B1853s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs